Classification and methodical features of fitness and wellness facilities - Beliak, Yu. I. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : health and fitness use a large arsenal of different sports and physical activity. Development of fitness industry promotes its expansion and requires classification and methodological features that lead to the use of appropriate fitness programs. Material : more than 60 literature and video of 42 prestigious international fitness - conventions lessons were analyzed. Results : the evolution of species fitness and wellness, as well as the character used in those funds. Conclusions : as a means of improving classification attribute fitness appropriate to use their orientation, according to which they are divided into aerobic, strength exercises that promote flexibility and psychomotor coordination. The main methodological features fitness facilities are highlighted: the variety and interchangeability, clear regulation, the ability to transform, to exercise a selective effect on the body, the ability to solve a wide range of tasks, innovation.